CRIME AGAINST WOMEN IN INDIA – ANALYSIS OF NEWS AND OFFICIAL STATISTICS TO FIND FACTORS INFLUENCING TEMPORAL PATTERNS - Dheenathayalan, K.; Savitha, K.K. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The environment we reside in can have a profound impact on our actions, particularly when it comes to criminal activity. The importance of studying the effects of surroundings on criminal behavior has become increasingly clear. There are three main types of environments, natural, physical and social. In this work, how the natural environment affects rate of crime against women in India has been discussed. India has four seasons namely winter, monsoon, summer, and autumn. News headlines come under the crime against women category with published date are extracted from Indian news websites like The Hindu, Times of India, etc. These news headlines are grouped under three different violent crime types, kidnap & abduction, rape and rape with murder. seasonality of crime was exposed with the help of extracted date and crime type. This study revealed that rate of three crime types were high in (monsoon) rainy season followed by winter and autumn respectively.